THE RELATIONSHIP BETWEEN PARENT-CHILD COMMUNICATION AND GADGET ADDICTION (A Psychological and Da'wah Communication Study) - Winda Kustiawan; Zulfan Affandi; Muqtada Ibrahim; Rifqi Prayogi Hidayat (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to analyze the relationship between parent-child communication patterns and the impact of gadget use on adolescents’ mental health and behavior. The research method employed is qualitative with a literature review approach, analyzing various relevant sources related to the research topic. The findings indicate that communication patterns between parents and children regarding gadget use are not linear or one-directional but rather conflicting. Gadget use can negatively affect children's mental health, leading to increased anxiety, stress, and gadget addiction. Tensions often arise due to differing perspectives between parents and children, reflecting authoritarian, permissive, and authoritative communication patterns. As a result, conflict becomes an inevitable outcome of excessive or uncontrolled gadget use. Conflict resolution involves providing understanding, effective communication from parents, and education for children so that they can use gadgets more wisely and responsibly.